2011
DOI: 10.1155/2011/167525
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of the Effectiveness of Two Different 10% Carbamide Peroxide Bleaching Products: A 6-Month Followup

Abstract: The purpose of this study was to evaluate the efficacy of two different 10% carbamide peroxide bleaching products just after treatment and after a 6-month follow-up period. Methods. Two 10% carbamide peroxide products (Opalescence PF and Nite White ACP) were applied nightly for 14 days, according to the manufacturers' instructions. The color of teeth 11 and 21 of thirty-four subjects having A2 or darker teeth were measured with a spectrophotometer (L ∗; a ∗; b ∗) before treatment, just after treatment (14 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
2
4
0
5
Order By: Relevance
“…( 1 ) and Table 1 ) can be attributed to the fact that the base-line color of the teeth was not a selection criteria and the whitening of enamel varies between subjects. Such a large spread of results during whitening has been reported previously [ 26 - 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…( 1 ) and Table 1 ) can be attributed to the fact that the base-line color of the teeth was not a selection criteria and the whitening of enamel varies between subjects. Such a large spread of results during whitening has been reported previously [ 26 - 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…There was statistical rebound in the color values of 10% CP/PF for all shades after 6 months follow‐up; however, this color difference was lower than 3.5, which showed that it was clinically acceptable. Different results were obtained from different trials in literature . Some authors reported no significant change in the color of bleached teeth with 10% CP after 2 years to 12 years, while Grobler and colleagues showed a significant rebound with 10% CP after 6 months.…”
Section: Discussionmentioning
confidence: 94%
“…Different results were obtained from different trials in literature. 27,28 Some authors reported no significant change in the color of bleached teeth with 10% CP after 2 years to 12 years, 5,24 while Grobler and colleagues 28 showed a significant rebound with 10% CP after 6 months. Similar to our results, no rebound in color was revealed after bleaching with a 9% HP preloaded tray system at a 3-month follow-up.…”
Section: A1mentioning
confidence: 99%
“…Literatürde, farklı araştırmalarda farklı sonuçlar elde edilmiştir. 26,27 Bazı araştırmacılar tarafından, 2 yıl ve 9-12 yıl sonra %10 KP ile beyazlatılan dişlerin renginde önemli bir değişiklik bildirilmemiştir. 5,24 Buna karşılık, Grobler ve ark., %10 KP uygulamasından 6 ay sonra istatistiksel olarak anlamlı bir geri dönüş olduğunu göstermişlerdir.…”
Section: -11unclassified
“…5,24 Buna karşılık, Grobler ve ark., %10 KP uygulamasından 6 ay sonra istatistiksel olarak anlamlı bir geri dönüş olduğunu göstermişlerdir. 27 Sonuçlarımıza benzer şekilde, 3 aylık izlem döneminde %9 HP içeren hazır kaşık ile uygulanan beyazlatma sistemi ile beyazlatma tedavisinden sonra renkte herhangi bir geri dönüş rapor edilmemiştir. 28 Çalışmamızdaki iki farklı beyazlatma sisteminden %10 KP/PF grubunun renk stabilitesinin daha başarısız oluşunun %10 KP/PF grubundaki dişlerin daha fazla renk değişimi gös-termesi ve bu nedenle renklenme riskinin bu grupta daha yüksek olmasına bağlanabileceği dü-şünülmektedir.…”
Section: -11unclassified